A Derrida reader : between the blinds - Derrida, Jacques; Kamuf, Peggy (New York [etc.] : Harvester Wheatsheaf, 1991)
In the English-speaking world, Jacques Derrida’s writings have most influenced the discipline of literary studies. Yet what has emerged since the initial phase of Derrida’s influence on the study of English literature, classed under the rubric of deconstruction, has often been disowned by Derrida. What, then, can Derrida teach us about literary language, about the rhetoric of literature, and about questions concerning style, form, and structure?

The Derrida Reader draws together a number of Derrida’s most interesting and idiosyncratic essays that treat literary language, the idea of the literary, and questions of poetics and poetry. The essays discuss single tropes or concepts, a figure such as metaphor, the ideas of titles and signatures, proper names, and Derrida’s thinking on such subjects as undecidability or aporia. The editor’s introduction is a demonstration in practice of how Derrida reads and how he adapts the act of reading to the text or figure in question. The introduction also outlines each essay’s main points, its usefulness for reading literary texts, and its particular area of interest. The Derrida Reader thus provides students of literature with a focused, contextualized, and readily understandable volume.
Str. 601-616: Bibliografija
Kazala
Keywords: filozofija jezika